Workplace Stress among Pediatricians in Benghazi Children Hospital - Eltarhuni , Ainas; El-Abidi , Jebril; Tawfeeq , Hajir (Libyan Journal of Medical and Applied Sciences, 2025)
Background: Health care workers are prone to stress as well as other occupational health risks. This study aimed to investigate the sources of job stress among pediatricians working at Benghazi Children Hospital and to determine its difference with personal characteristics. Materials and Methods: A cross-sectional descriptive study was carried out at Benghazi Children Hospital. A random sample of 132 pediatricians was selected from 200 pediatricians working in Benghazi Children Hospital. Usable returns were received from 128 pediatricians. A self-administered questionnaire included two main parts: personal characteristics of physicians and 41 work-related stress questions. The statistical tool SPSS was used for the analysis. Descriptive statistics, T-test, and one-way ANOVA were used to analyze the data generated. Results: The results showed half of the pediatricians were categorized as having a moderate level of stress, followed by slightly less than half of them having a high level of job stress. According to the statements, responsibility for child life, the possibility of exposure to infection, workload, and inadequate income compared to qualification level were the commonest sources of stress. Significant differences were found between stress and gender, age, experience, and professional position. There was no significant difference between stress and marital status, qualification, and monthly income. Conclusion: Study results concluded that pediatricians in the target hospital experienced moderate to high stress. To reduce job stress, it was recommended that workload should be minimized and the presence of seniors while dealing with critical patients assisted in reducing the stress level among junior physicians.